Development of national action plans on business and human rights and the status of the plans of action CSR: Spain and the Nordic Countries - Rojas Buendía, María del Mar (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2015)
Nordic countries like Denmark, Finland, Sweden, Norway and Iceland, with highly developed welfare states, are at the head of the existing rankings in terms of Corporate Social Responsibility (CSR) and sustainability. In addition to its high level of awareness, their companies, beyond the mere creation of economic value, they seek to maximize the welfare of the whole society, investing today in the development of future activity without compromising the needs of future generations. Spain, halfway between the voluntary adoption of CSR strategies and the need for regulation of minimum, addresses today the implementation of a plan that includes concrete measures focused, following the Guiding Principles which reflect the current international law, the duty of the State to protect, the duty of corporate to respect and access to legal and other redress mechanisms, and which conditions any support from the Government to respect human rights by those companies that request it. The present study is national HR policies and will consider the need for a new International Treaty on Business and Human Rights on the world stage. But it should hold, within the analysis proposed here, on the one hand, the voluntary initiative of the State Government to develop Business Plans and Human Rights (HR) and CSR; and, second, that the framework is to respect the established global or international level; if we want to understand the willingness of some countries and the neglect of others; and their policies governments, CSR.
Keywords: business and human rights; national and international policies; CSR